2019
DOI: 10.1007/s00204-019-02572-w
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study

Abstract: Aflatoxin B1 (AFB1), a food contaminant derived from Aspergillus fungi, has been reported to cause hepatic immunotoxicity via inflammatory infiltration and cytokines release. As a pro-inflammatory factor, cyclooxygenase-2 (COX-2) is widely involved in liver inflammation induced by xenobiotics. However, the mechanism by which AFB1-induced COX-2 regulates liver inflammatory injury via hepatocytes-Kupffer cells (KCs) crosstalk remains unclear and requires further elucidation. Here, we established a COX-2 upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 49 publications
(58 reference statements)
4
54
0
Order By: Relevance
“… 28 Zhang et al. 9 reported that the severity of AFB1-induced liver inflammatory injury in mice was significantly alleviated by downregulating NLRP3 expression through inhibition of cyclooxygenase-2. These results imply that persistent activation of the NLRP3 inflammasome is a critical factor for instigating tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Zhang et al. 9 reported that the severity of AFB1-induced liver inflammatory injury in mice was significantly alleviated by downregulating NLRP3 expression through inhibition of cyclooxygenase-2. These results imply that persistent activation of the NLRP3 inflammasome is a critical factor for instigating tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, AFB1 was found to activate the NLRP3 inflammasome in primary hepatocytes and Kupffer cells, leading to liver inflammatory injury. 9 It seems reasonable that a similar activation method may be induced by AFB1 in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 upregulates COX-2 which activates the inflammasome leading to tumor-promoting inflammation. In contrast, celecoxib reduced this inflammation demonstrating the regulation of inflammation by eicosanoids and inflammatory mediators ( Zhang et al, 2019 ). Additionally, etodolac, a COX-2 inhibitor, suppresses N -nitrosobis(2-oxopropyl)amine (BoP)-induced experimental biliary carcinogenesis ( Tsuneoka et al, 2005 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In addition, IL-1 β can induce the production of TNF- α 49 , 50 , another key cytokine involved in amplifying and perpetuating the liver damage by triggering liver inflammation, neutrophils, and proinflammatory macrophage recruitment 51 , 52 , 53 , 54 . Moreover, NLRP3 inflammasome activation also leads to caspase-1-dependent pyroptosis 8 , this distinct form of programmed cell death could mediate liver injury 47 , 55 , 56 . In addition, one of important upstream signaling of NLRP3 inflammasome activation is ROS production 57 , 58 , which can lead to mitochondrial dysfunction through an intracellular oxidant stress in hepatocytes leading mainly to oncotic necrosis and less apoptosis 52 , 59 .…”
Section: Discussionmentioning
confidence: 99%